A new way to play music together: The Continuator in the classroom. (May 2014) - Ferrari, Laura; Addessi, Anna Rita
This article describes a didactic experience concerning the interaction between young children and the Continuator, an Interactive Reflexive Musical System (IRMS) elaborated at SONY- Computer Science Laboratory in Paris. The general aim was to analyse whether and how the Continuator can be used in the kindergartner during the daily school activities and the role of the teacher in the context of free play and in guided activities with the system. The experience took place in Bologna (Italy) and involved 18 children aged 3–5 years. The children learned to dialogue musically with the system and to manage various kinds of collaborative play. These factors gave rise to some particularly attentive and prolonged bouts of listening, stimulating the children to think in terms of sound and developing a genuine desire to "play" with music. This experience shows how the Continuator could represent a versatile device capable of enhancing musical creativity and exploration in a classroom setting.